Daugavpils musically dramatic theatre (1959-1962) - Geikina, Silvija (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
The history of Daugavpils Dramatic Theatre is one of the most original and peculiar theatre histories in Latvia. To begin discussing it, historians usually mention the Russian Theatre led by the colonel and the main engineer of Daugavpils Fortress Nikolaj Hagelstrom in 1850s. It was operating for several decades collaborating with tsarist Russian army troops staying at Daugavpils Fortress. During the times of Latvian independency from 1920s to 40s there was a successfully operating Daugavpils Latvian Theatre Company in the city. Russian audiences attended Latvian shows in great numbers and supported Russian amateur theatres which were very active in this period of time. After the Second World War, Daugavpils Latvian Theatre did not resume itself. The reasons for liquidating the Latvian Company in Daugavpils included the decrease of Latvian population, and the negative attitude of Latvian SSR Ministry of Culture and the council of Daugavpils regarding Latvian cultural activities in Latgale. This attitude changed a little in the late 1950s. It had become more favourable, which was wisely and diplomatically taken advantage of by Voldemars Kalpins – Latvian SSR deputy minister of culture at the time and the minister of culture and foreign affairs from 1959 to 1962. A popular viewpoint during those years was that creating a Latvian theatre in Daugavpils would not be just a creation of an art building, but would in fact serve a great purpose then and in the future – saving Latvian culture and identity in Latgale. This brings to a conclusion that the operation of Daugavpils Musically Dramatic Theatre (1959-1962) is closely connected to the socio-political situation in Latvia during 1950s and to the beginning of the national- communistic movement. The communist party of the time made a number of decisions about maintaining Latvian language and culture. Special attention was paid to recreating Latvian culture in Latgale. After the defeat of the national-communistic movement and the dismissal of many leading party members in early 1960s, the support for Latvianising Latgale diminished. After not receiving the needed support from neither the leading republic officials nor from the city of Daugavpils, the theatre was forced to close down. The aims of the study: to explore the Daugavpils Musically Dramatic Theatre activities since its creation in 1959 until its closure in 1962; to find out the socio-political situation in Latvia during the end of 1950s leading to the possible emergence of a new theatre in Latgale; get to know the theatre’s repertory policy, dramatic and musical troupes and their building principles as well as theatrical artistic explorations during 1950s/60s. The used methods: media analysis method and interview.